Why Can’t My Child Play Too? Current Challenges of Public Playgrounds for Children with Disabilities. - Kathleen Tait; Peng Liang; Sue Silveira (Education Sciences)
Current Australian legislation promotes playground inclusion for all children, and playgrounds serve as local, safe, and vital spaces for children of all ages to play. The World Health Organisation International Classification of Functioning, Disability and Health, Children and Youth Version states that play is a key activity to engage children with disability in various areas of their lives, and there is no doubt that playgrounds can promote community and social engagement for all children. Consequently, accessible playgrounds are important because they can offer motor, psychological, and social skill development in a fun-filled environment. Nonetheless, some children encounter challenges in playground settings. Surprisingly, very little research has been conducted in Australia on the experiences of children with disabilities in public playgrounds. According to the National Autism Strategy announced by the Australian Government in 2022, there is a growing number of Australians on the autism spectrum. For many individuals with an autistic spectrum disorder (ASD), life outcomes in education, health, and family functioning are worse than they should be. Consequently, while this paper addresses a general perspective of inclusive playground experience for children with disabilities, there is also a focus on the experiences of children with ASD in playgrounds. As a result, this literature review begins with an introduction to the prevalence of autistic spectrum disorder and its associated characteristics. It presents existing research on play, examining various playground factors that impact the experiences of children with disabilities, including ASD. In addition, the role of parents/carers in influencing the outdoor experiences of children with disability is also explored. In conclusion, this paper summarises key findings and proposes relevant research questions to address these gaps.